In situ encapsulation of pt nanoarchitectures of varying morphologies in mesoporous compounds - Prashar, Atul K.; Hodgkins, Robert P.; Chandran, Jima N.; Rajamohanan, P. R.; Devi, R. Nandini (Chemistry of Materials, 2010)
Nanoparticle morphology could be engineered and fine-tuned based on a novel in situ template method Different shapes of platinum nanoparticles were obtained from very low concentrations of precursors and could be isolated exclusively inside the mesochannels of SBA-15 This was achieved by dispersing a platinum precursor in surfactant modified polymer to different extents and using these composite materials as templates for the formation of mesoporous silica [PtCl(6)](2-) interacts with the cationic headgroup of the surfactant and facilitates the isolation of precursors within the composite template leading to the formation of nanoparticles molded by the walls of the mesochannels when calcined When this [PtCl(6)](2-)-surfactant-polymer micelle composite is aged for different duration, Pt nanoparticles of various morphologies like spheroids, nano rugby balls, and nanorods are obtained